2015
DOI: 10.1021/acs.analchem.5b02066
|View full text |Cite
|
Sign up to set email alerts
|

Negative Ion Laser Desorption/Ionization Time-of-Flight Mass Spectrometric Analysis of Small Molecules Using Graphitic Carbon Nitride Nanosheet Matrix

Abstract: Ultrathin graphitic carbon nitride (g-C 3 N 4 ) nanosheets served as a novel matrix for the detection of small molecules by negative ion matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) was described for the first time. In comparison with conventional organic matrices and graphene matrix, the use of g-C 3 N 4 nanosheet matrix showed free matrix background interference and increased signal intensity in the analysis of amino acids, nucleobases, peptides, bisphenols (BPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 38 publications
2
49
0
1
Order By: Relevance
“…S4-S7 and Table S3, ESI †). This meant that the LODs for most of the analytes achieved in the present study were comparable to, or better than, those reported in the literature, 8,13,17 indicating the high sensitivity of the established method. Moreover, the perfect homogeneity of the UiO-66-NH 2 @Au matrix results in good reproducibility.…”
supporting
confidence: 84%
“…S4-S7 and Table S3, ESI †). This meant that the LODs for most of the analytes achieved in the present study were comparable to, or better than, those reported in the literature, 8,13,17 indicating the high sensitivity of the established method. Moreover, the perfect homogeneity of the UiO-66-NH 2 @Au matrix results in good reproducibility.…”
supporting
confidence: 84%
“…Recently, Lin et al [50] used g-C 3 N 4 nanosheets as an assisted matrix of LDI for analyzing various different low molecular weight compounds. Mass spectra with free background interference and improved signal intensity were obtained for analyzing a series of small molecules including amino acids, nucleobases, peptides, bisphenols, and nitro-polycyclic aromatic hydrocarbons (nitro-PAHs) in the negative mode.…”
Section: Nanomaterial-assisted Ldi Methods Developmentmentioning
confidence: 99%
“…In particular, g‐C 3 N 4 nanosheets with nanoscale and atomic‐scale thickness possess of lamellar graphite structure, and strong UV adsorption capability, it is believed that the g‐C 3 N 4 nanosheets can satisfy the criteria to serve as a matrix for LDI‐TOF MS . Inspired by its exceptional properties, our group recently prepared ultrathin g‐C 3 N 4 nanosheets by ultrasonication‐assisted liquid exfoliation of bulk g‐C 3 N 4 in water and first applied it as matrix for LDI‐TOF MS. As shown in Figure , the obtained nanosheets were dispersed stably in water, even upon standing for 2 months. Besides, the transmission electron microscopy (TEM) and atomic force microscopy (AFM) images confirmed that the nanosheets were well separated from each other with the thickness of 2 nm and the diameter of ∼200 nm, respectively.…”
Section: Nanostructured Substrates For Negative Ion Ldi‐tof Msmentioning
confidence: 99%
“…E, UV‐visible spectrum of bulk g‐C 3 N 4 and nanosheets. Reprinted with permission from Lin et al Copyright 2015 American Chemical Society…”
Section: Nanostructured Substrates For Negative Ion Ldi‐tof Msmentioning
confidence: 99%